Study & Analysis of Statistical Methods and Their Application to Career Prediction System - Lokesh S, Katore; Bhakti S, Ratnaparkhi; Jayant S, Umale; Upadhyay, Niharika (International Journal of Computer Sciences and Engineering, 2015)
Now a day’s prediction systems are key software systems in business and social contexts. We observe the change in decision making and success obtained by organization and individuals due to accurate prediction systems. Various algorithms and theories are used by researchers to formulate prediction systems. We feel the study of state of art methods for design of prediction systems is highly necessary. This work studies the mathematical approaches used for prediction. We propose the application of Rough Set Theory for design of career prediction system.